18th Convention of the California State Farm Insurance Agents - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 18th annual convention of California State Farm insurance agents, held October 20-21, 1949 in San Jose, California.